A tachykinin-like neuroendocrine signalling axis couples central serotonin action and nutrient sensing with peripheral lipid metabolism - Lavinia Palamiuc (Nature Portfolio, 2017)
Serotonin is a potent stimulator of fat loss and energy expenditure in several species, includingC. elegans. Here, Palamiuc et al. identify the neuropeptide, FP-7, and its receptor in the intestine, NRP-22 as mediators of serotonergic body fat loss in worms.